Discovery of Selective Small‐Molecule Activators of a Bacterial Glycoside Hydrolase1. Issue 49 (7th October 2014) - Darby, John F.; Landström, Jens; Roth, Christian; He, Yuan; Davies, Gideon J.; Hubbard, Roderick E.
Abstract Fragment‐based approaches are used routinely to discover enzyme inhibitors as cellular tools and potential therapeutic agents. There have been few reports, however, of the discovery of small‐molecule enzyme activators. Herein, we describe the discovery and characterization of small‐molecule activators of a glycoside hydrolase (a bacterial O‐GlcNAc hydrolase). A ligand‐observed NMR screen of a library of commercially available fragments identified an enzyme activator which yielded an approximate 90 % increase in kcat/KM values (kcat=catalytic rate constant; KM=Michaelis constant). This compound binds to the enzyme in close proximity to the catalytic center. Evolution of the initial hits led to improved compounds that behave as nonessential activators effecting both KM and Vmax values (Vmax=maximum rate of reaction). The compounds appear to stabilize an active "closed" form of the enzyme. Such activators could offer an orthogonal alternative to enzyme inhibitors for perturbation of enzyme activity in vivo, and could also be used for glycoside hydrolase activation in many industrial processes.